He Effect Of Technical And Fundamental Analysis On Stock Prices - Kuncoro Hadi; Andalan Tri Ratnawati (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This study aims to analyze the effect of technical and fundamental analysis on stock prices by conducting an empirical study on pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange. Eight companies that meet the criteria were selected, and financial reports from 2017-2021 were used. This research uses descriptive analysis with quantitative data analysis in the form of descriptive statistics for each variable used. Technical analysis was performed using the Composite Stock Price Index and trading volume indicators, while fundamental analysis was performed using the Earning Per Share (EPS), Price Earning Ratio (PER), and Stock Price indicators. The research results showed that EPS and PER have a significant positive effect on stock prices, while the Composite Stock Price Index has a negative and insignificant effect, and the trading volume indicator has a positive and insignificant effect.